Investigation of type 1 diabetes and coeliac disease susceptibility loci for association with juvenile idiopathic arthritis. Issue 12 (20th July 2010) - Hinks, Anne; Martin, Paul; Flynn, Edward; Eyre, Steve; Packham, Jon; Barton, Anne; Worthington, Jane; Thomson, Wendy
Abstract : Background: There is strong evidence suggesting that juvenile idiopathic arthritis (JIA) shares many susceptibility loci with other autoimmune diseases. Objective: To investigate variants robustly associated with type 1 diabetes (T1D) or coeliac disease (CD) for association with JIA. Methods: Sixteen single-nucleotide polymorphisms (SNPs) already identified as susceptibility loci for T1D/CD were selected for genotyping in patients with JIA (n=1054) and healthy controls (n=3129). Genotype and allele frequencies were compared using the Cochrane–Armitage trend test implemented in PLINK. Results: One SNP in the LPP gene, rs1464510, showed significant association with JIA (ptrend =0.002, OR=1.18, 95% CI 1.06 to 1.30). A second SNP, rs653178 in ATXN2, also showed nominal evidence for association with JIA (ptrend =0.02, OR=1.13, 95% CI 1.02 to 1.25). The SNP, rs17810546, in IL12A showed subtype-specific association with enthesitis-related arthritis (ERA) subtype (ptrend =0.005, OR=1.88, 95% CI 1.2 to 2.94). Conclusions: Evidence for a novel JIA susceptibility locus, LPP, is presented. Association at the SH2B3/ATXN2 locus, previously reported to be associated with JIA in a US series, also supports this region as contributing to JIA susceptibility. In addition, a subtype-specific association of IL12A with ERA is identified. All findings will require validation in independent JIA cohorts.